Perbandingan Penggunaan Bahasa Asing Dan Bahasa Indonesia di Ruang Publik (Mall Tunjungan Plaza Surabaya) - Mery Irene T; Jellyta Amelia Puspita Condro; Sefira Syadza Andina; Farida Indi Nur An-nisa; Azmil Umur (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of the research conducted was to examine the number of foreign languages used in Tunjungan Plaza Surabaya Mall whose meaning is not understood by certain circles. The research method used is a qualitative method and a literature method with documentation techniques. The results of this study are that the use of foreign languages in the Tunjungan Plaza Mall is almost evenly distributed which can threaten the existence of the Indonesian language. Therefore, good use of Indonesian is necessary to maintain the position of Indonesian as the national language.